TINJAUAN YURIDIS PENGHAPUSAN PRESIDENTIAL THRESHOLD 20% DALAM SISTEM PEMILU DI INDONESIA (STUDI KASUS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 62/PUU-XXII/2024) - Abd Rahman Darmawangsa; Agung Sakti Pribadi; M. Asyharuddin (Bajang Institute, 2025)
The constitutional court's decision in early 2025 to abolish the Presidential Threshold provision is a significant turning point in the development of Indonesian politics. Previously, this rule required political parties to hold at least 20% of seats in the House of Representatives or obtain 25% of the national valid votes to be able to nominate a presidential candidate pair. The court found that the rule was not in line with the spirit of the constitution and the principle of popular sovereignty. With the removal of this provision, more political parties have the opportunity to nominate candidates, thus increasing inclusivity in the conduct of elections. Nevertheless, a crucial challenge arises in maintaining the quality and credibility of presidential candidates, given the increasing risk of identity politics. This research uses a normative legal method with a legislative, case study, conceptual, and comparative approach. The analysis results show that the removal of the threshold provides wider access for political parties, strengthens the principle of equality, and promotes the realization of inclusive democracy.